Temporal Asynchrony but Not Total Energy Nor Duration Improves the Judgment of Numerosity in Electrotactile Stimulation - Nataletti, Sara; Leo, Fabrizio; Seminara, Lucia; Trompetto, Carlo; Valle, Maurizio; Dosen, Strahinja; Brayda, Luca (Frontiers in Bioengineering and Biotechnology, 2020)
Stroke patients suffer from impairments of both motor and somatosensory functions. The functional recovery of upper extremities is one of the primary goals of rehabilitation programs. Additional somatosensory deficits limit sensorimotor function and significantly affect its recovery after this neuromotor injury. Sensory substitution systems, providing tactile feedback, might facilitate manipulation capability and improve patient’s dexterity during grasping movements. As a first step towards this aim, we evaluated the ability of healthy subjects in exploiting electrotactile feedback on the shoulder to determine the number of perceived stimuli in numerosity judgment tasks. During the experiment, we compared four different stimulation patterns (two simultaneous: short and long, intermittent and sequential) differing in total duration, total energy or temporal synchrony. The experiment confirmed that the enumeration ability of electrotactile stimuli decreases with increasing the number of active electrodes. Furthermore, we found that, in electrotactile stimulation, the temporal coding schemes and not total energy or duration modulates the accuracy in numerosity judgment. More precisely, the sequential condition resulted in significantly better numerosity discrimination than intermittent and simultaneous stimulation. These findings, together with the fact that the shoulder appeared to be a feasible stimulation site to address tactile information via electrotactile feedback, can serve as a guide to deliver tactile feedback to proximal areas in stroke survivors who lack sensory integrity in distal areas of their affected arm, but retain motor skills.